Effects of frozen storage period on the biochemical and microbial quality of little tunny Euthynnus alletteratus (Latakia University Journal -Biological Sciences Series, 2025)
The aim of this study was to evaluate the biochemical and microbial quality of the muscle of little tunny Euthynnus alletteratus during different storage periods (15 days, 30 days and 60 days) under frozen storage conditions (-18 °C). Fresh fish samples were collected from the fish marketplace of Latakia, transported in refrigerated condition to the laboratory. The weight of the fish individuals ranged between 250-300 g. Samples were cleaned and eviscerated, and scales were removed, then frozen at (-35 C°) for five hours and finally stored at (-18 C°), and their quality was assessed during different storing periods. Moisture, ash, protein and fat ratio were estimated before and after freezing.The results showed significant changes in the chemical composition of frozen muscle of the fish species studied, and their values varied significantly throughout the storage period (p